Promotional Games Increase Consumer Conversion Rates and Spending - Hock, Stefan J; Bagchi, Rajesh; Anderson, Thomas M (Journal of Consumer Research, 2020)
Abstract Promotional games are used frequently in retail stores and online. While prior literature has focused on antecedents of promotional games, such as how individual differences induce game participation, little is known about post-winning decision making or its underlying processes. This study offers findings from seven studies to provide a detailed perspective on how promotional games increase consumer conversion rates and spending. The effect of winning a discount on conversion rates and spending is multiply determined and occurs via perceptions of luck and store affective attitude, and via perceptions of luck alone and store affective attitude alone. In order to get a more nuanced understanding of the underlying processes and to delineate theoretically driven boundary conditions for this novel effect, the authors subsequently analyze the two individual pathways through perceptions of luck and store affective attitude in isolation. Thereby, they contribute to the literature on pricing and promotions by providing a detailed understanding on how winning a promotional discount leads to a different set of consumer inferences relative to an equivalent straight discount, and to the literature on the role of luck in consumer behavior by providing a nuanced understanding of how luck operates in this common consumer context.